Kantor Sewa Di Pekanbaru Dengan Pendekatan Arsitektur Postmodern - Frendi Dwi Wardana Putra; Wahyu Hidayat; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
In managing business and administrative, office becomes an important aspect for a company. To built a private office, company need a large amount of investment and sometimes can be a hard choices for particular of them. Therefor rental office become an alternative to solve this issue. For attract companies to be a tenant, rental office design take a part to give them prestigious values and giving great image brand for their company. Postmodern Architecture chosen to be applied for the Rental Office in Pekanbaru as a design approach. Using human’s movement as concept to get their flexibility and perception similiar to human’s movement with apply methapor as chosen design method in Postmodern Architecture. To get dynamic design exploration from the concept is transforms the movement to become architectural form on purpose to get proper rental office for tenants. And the design elements from The Rental Office in Pekanbaru with Postmodern Architecture is aplied to zoning, outdoor planning, mass order, indoor planning, and structure. Keywords: Rent Office, Movement, Methapor, Postmodern Architecture.